Acute pulmonary hypertension as a symptom of Bard’s syndrome and pulmonary lymphangitis carcinomatosa – rare manifestation of malignant gastric cancer - Mazur, Danuta; Romanek, Janusz; Filip, Rafał; Przybylski, Andrzej (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Acute pulmonary hypertension leading to right ventricular failure and circulatory collapse is usually caused by a pulmonary embolism. However, in extremely rare cases, similar clinical manifestations can be related to another diseases, such as lymphangitis carcinomatosa. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The purpose of this paper is to report on the case of a 29-year-old male patient presented with rapidly progressing dyspnoea. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. The diagnosis of pulmonary embolism was made on the basis of echocardiographic signs of pulmonary hypertension and right ventricular (RV) dilatation, and the recommended therapy was introduced. On the suspicion of bronchopneumonia, antibiotics and steroids were applied. However, the previously stated diagnosis of pulmonary embolism was not confirmed by the angio-CT scan, which showed small diffusive lung parenchyma intra-biliary nodules (ground glass opacity) with the peripheral appearance of a tree-in-bud sign. Consecutive CT of pelvis and abdomen along with endoscopy revealed a metastatic gastric cancer with the presence of lymphangitis carcinomatosa and miliary dissemination to the lungs. The presence of pulmonary metastases in the course of disseminated gastric cancer is known in literature as Bard’s syndrome. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Extrapulmonary malignancies, particularly gastric cancer, should be taken into consideration in differential diagnosis in patients with an acute right ventricular failure and nonspecific lesions in the respiratory system.